2013 IEEE International Symposium on Information Theory 2013
DOI: 10.1109/isit.2013.6620369
|View full text |Cite
|
Sign up to set email alerts
|

On the capacity region for index coding

Abstract: Abstract-A new inner bound on the capacity region of the general index coding problem is established. Unlike most existing bounds that are based on graph theoretic or algebraic tools, the bound relies on a random coding scheme and optimal decoding, and has a simple polymatroidal single-letter expression. The utility of the inner bound is demonstrated by examples that include the capacity region for all index coding problems with up to five messages (there are 9846 nonisomorphic ones).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
217
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 146 publications
(223 citation statements)
references
References 21 publications
5
217
1
Order By: Relevance
“…By setting the rate for each receiver the same, their capacity region result yields the symmetric capacity, which is the inverse of the optimal broadcast rate β defined in Definition 4. The obtained symmetric capacity result in the case of n = m ≤ 5 in [4] can be used to obtain the symmetric capacity in the case of n < m ≤ 5, based on Theorem 1 and the result (P 2 ) ≥ (P 1 (G cl (P 2 ))) by Lubetzky and Stav [6]. There exist 9846 non-isomorphic C 1 -index coding problems with n = m ≤ 5 [4].…”
Section: Ieee International Symposium On Information Theorymentioning
confidence: 96%
See 4 more Smart Citations
“…By setting the rate for each receiver the same, their capacity region result yields the symmetric capacity, which is the inverse of the optimal broadcast rate β defined in Definition 4. The obtained symmetric capacity result in the case of n = m ≤ 5 in [4] can be used to obtain the symmetric capacity in the case of n < m ≤ 5, based on Theorem 1 and the result (P 2 ) ≥ (P 1 (G cl (P 2 ))) by Lubetzky and Stav [6]. There exist 9846 non-isomorphic C 1 -index coding problems with n = m ≤ 5 [4].…”
Section: Ieee International Symposium On Information Theorymentioning
confidence: 96%
“…However, in [6], Lubetzky and Stav showed that there exist certain cases in which nonlinear index coding strictly outperforms linear index coding. In [4], Arbabjolfaei et al obtained the capacity region for index coding with up to five receivers for C 1 . By using this result and setting all user rates the same, one can obtain the symmetric capacity for C 1 with up to five receivers.…”
Section: A Related Workmentioning
confidence: 99%
See 3 more Smart Citations